Minimal incision palatoplasty with or without muscle reconstruction in patients with isolated cleft palate: a cast and medical records analysis. (15th December 2017) - Parikakis, Konstantinos A; Larson, Ola; Larson, Margareta; Karsten, Agneta
Summary: Objectives: To compare the minimal incision (MI) technique with the minimal incision including muscle reconstruction (MMI) technique regarding surgical complications and dentoalveolar status at 5 years of age. Subjects and method: A consecutive series of 202 Caucasian non-syndromic children (apart from Pierre Robin Sequence) born with isolated cleft palate between 1987 and 2007 and treated with MI ( n = 78) or MMI ( n = 102) palatoplasty at a mean age of 12.7 (SD = 1.43) months in Stockholm. Twenty-two patients did not fulfill the inclusion criteria. The patients were divided into two subgroups: clefts within the soft palate only (small cleft, n = 50) and clefts within the hard and soft palate (big cleft, n = 130). Dental relations, structure of the palatal mucosa, and height of the palatal vault at 5 (mean age 5.3, range: 4.4–6.9) years of age were studied using plaster models. Time for surgery, blood loss, complications in the immediate postoperative period, frequency of fistulas, and additional pharyngeal flap surgery were evaluated. Student's t -test, chi-square test and 95 per cent confidence intervals were calculated. Results: MMI compared to MI technique result in statistically significant increased operation time, less need for pharyngeal flap surgery, and to shallower palatal vault. Big clefts result in statistically significant increased operation time and need for pharyngeal flap surgery. Dental relations were the same in all groups. Limitations: Retrospective single centre study, limited sample size, more than one surgeon. Conclusions: The muscle reconstruction results in a reduced subsequent need for pharyngeal flap surgery, but to shallower palatal vault and demand for almost double operation time. The dental relations were the same in all groups.